(3cGed GdUfGYI GdWHjIs - (3Ydj Hf YHGS GdeLhSj,fMh (B400 (3g`s
(3ChdgG (B:s
(3GdHGH GdChd ef GdebGd GdSGHYI ai LedI GdcdGe Ydi OdGFd GdCeQGV hJbSjegG bO HjfG ai cd hGMO ef GdCYQGV hGdCSHGH GdaGYdI dgG hgj GdCeQGV hgh GdHGH GdPi SejfGg CSHGH GdCYQGV s
(3BNQgG (B:s
(3hEPG cGf eY hLY GdfbQS hQe aEfg hjScf ai CQHYjf jhekG , gPG EPG cGfJ GdeGOI ZdjXI s
(3bWYI KGfjI GdLRA GdChd GdYdei ef fSNI NGeSIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B317 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B162s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B191 ; (3eLdI eYgO GdeNWhWGJ (B- (3GdLRA (B5 - (3U (B328 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(387(3c(B) s
Keywords: (3GdWHs